Identifikasi Keberadaan Serovar Bakteri Leptospira pada Serum Darah Suspek Leptospirosis di Kecamatan Manggala Kota Makassar - Sri Indi Rahmadanti Haryono; Syamsuar Manyullei; Hasnawati Amqam (Faculty of Public Health, Hasanuddin University, Makassar, 2020)
Leptospirosis or also commonly called Weil disease is an acute infectious disease that can attack humans and animals and is classified as a zoonotic disease. Leptospirosis is caused by bacteria of the genus Leptospira found in rodents. This study aims to determine the presence of Leptospira bacteria serovar in blood serum suspected of leptospirosis using the Microscopic Aglutination Test (MAT) method. This type of research is descriptive observational using accidental sampling technique with a total of 31 samples. Sampling was conducted at the Antang Community Health Center, Batua Health Center and Bangkala Health Center in Manggala District for two weeks. Data analysis in this research is descriptive in which the results are presented through tables and narratives. The results of MAT examination on blood serum yielded eleven positive samples of Leptospira (37%) with serovar Hebdomadis, Djasiman, Mini, Icterohaemorrhagiae, Bangkingan and Bataviae. The presence of Leptospira bacteria in the blood serum of suspected individuals using the MAT Method obtained 11 samples of positive blood serum. Need to conduct and improve special counseling activities about leptospirosis and diagnosis enforcement in the community or workers who experience symptoms or suspected leptospirosis.